2009
DOI: 10.1111/j.1365-2486.2009.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated environmental change on alpine soil arthropods

Abstract: The effects of environmental change on soil animal communities are poorly known. Norwegian mountains are subject to both atmospheric nitrogen deposition and increased temperature. In a nutrient poor alpine Dryas heath in south Norway, soil arthropods were studied after 4 years of simulated environmental change by warming and/or nutrient addition. Warming alone only affected three low-density Collembola species, while nutrient addition, with or without warming, greatly changed the dominance hierarchy of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 48 publications
(60 reference statements)
1
50
1
Order By: Relevance
“…A similar, but short-term, study to this found no effects of four years of experimental warming on oribatid mites15. However, the life cycle of oribatid mites often spans several years39, and this, in combination with high weather variability between years, may have masked the effects of the limited experimental warming applied in that study1525.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A similar, but short-term, study to this found no effects of four years of experimental warming on oribatid mites15. However, the life cycle of oribatid mites often spans several years39, and this, in combination with high weather variability between years, may have masked the effects of the limited experimental warming applied in that study1525.…”
Section: Discussionmentioning
confidence: 52%
“…However, the life cycle of oribatid mites often spans several years39, and this, in combination with high weather variability between years, may have masked the effects of the limited experimental warming applied in that study1525. This interaction between between-year variability and experimental warming effect has previously been demonstrated in a short-term study which found that the warming effect on soil fauna depended on whether the summer was relatively warm and dry, or cool and wet57.…”
Section: Discussionmentioning
confidence: 84%
“…Other organism groups may remain resistant or may be similarly affected, which would be of particular concern owing to the above-average level of endemic invertebrates compared to elevations below the timberline in the Alps (Rabitsch et al 2016). For alpine soil arthropod abundance, experimental warming was most effective when combined with nutrient addition (Hågvar and Klanderud 2009), whereas a long-term warming experiment had no effect on richness and abundance of springtails in alpine subarctic ecosystems (Alatalo, Jägerbrand, and Čuchta 2015). Changes in occurrence and activities of microorganisms would be especially relevant to climate change considering their attributes as key players for methane formation and consumption, belonging to methanogenic archaea and methanotrophic bacteria, respectively (Crutzen and Lelieveld 2001;Hofmann et al 2016b;Praeg, Wagner, and Illmer 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A global increase of temperature will lead to an increase of ecosystem productivity in the Alps (Theurillat and Guisan, 2001), accelerating forest regeneration following land abandonment and thus loss of habitat for alpine and subalpine herbaceous species as E. alpinum (Dirnbock et al, 2003;Engler et al, 2011). Climate warming will also lead to modifications in species interaction, community dynamics and productivity, and ecosystem processes (Araujo and Luoto, 2007;Easterling et al, 2000;Hagvar and Klanderud, 2009;Klanderud, 2010). Some drought-tolerant grasses as Festuca paniculata (growing at high density in the DES site) may benefit from an increasingly drier and hotter climate and outcompete E. alpinum (Sandra Lavorel, Laboratoire d'Ecologie Alpine, unpublished manuscript).…”
Section: Impact Of the 2003 Heatwave On Vital Rates And Population Grmentioning
confidence: 99%